APPLICATION OF VISIBLE LIGHT COMMUNICATION (VLC) INVARIOUS AREAS: SURVEY - Mamatnabiyev, Zh.; Galiyev, M. (Journal of Emerging Technologies and Computing, 2024)
Optical wireless communication allows communication of ultraviolet, infrared, or visible light to carry a signal. Visible light communication (VLC) is a member of optical wireless communication that operates in visible band from 390 nm to 750 nm range. VLC uses light emitting diodes (LED) that is pulsed at very high speed. VLC is known as next potential communication tool that has made tremendous improvement in wireless communication technologies. Possible applications areas of VLC are underwater communication, Li-Fi, vehicle to vehicle communication, in-house applications, etc. use features of VLC that allows to make an attractive area of research. In this work, due to features that VLC offers, possible application areas are presented and discussed.